Cultivares del Zea mays maíz híbrido y criollo con dos frecuencias de corte y su efecto en el rendimiento de forraje en Zungarococha, Perú - 2020 - Arbitro Collazos, Ana del Carmen (2022)
The research work was carried out at the National University of the Peruvian Amazon in the Faculty of Agronomy in the Cattle Project on the Zungarococha Farm, entitled "CULTIVARS OF Zea mays HYBRID AND CREOLE CORN WITH TWO CUTTING FREQUENCIES AND THEIR EFFECT ON YIELD OF FORAGE IN ZUNGAROCOCHA, PERU - 2020”. The evaluations were carried out at the tenth week of the beginning of the research work, with plots of 3 m x 1.2 m (3.6 m2) and an experimental area of 141.1 m2. With a Random Complete Block Design (D.B.C.A), with five treatments and four repetitions, the treatments under study were: T1 (MH1FC1), T2 (MH1FC2), T3 (MC2FC1) and T4 (MC2FC2), where MH1= HYBRID, MC2= CRIOLLO, FC1= 45 days after sowing and FC2= 60 days after sowing, where the following results were achieved: in height of 191.02 cm, green matter of 3.85 kg/m2, dry matter of 0.80 kg/m2 , green matter yield of 13.86 kilos per plot and green matter yield of 38,500 kilos per hectare. In this sense, it was shown that at least one of the two cutting frequencies together with the investigated maize cultivar, significantly influenced the variables at 45 and 60 days.